Reflecting Sunlight: Recommendations for Solar Geoengineering Research and Research Governance - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Climate change is creating impacts that are widespread and severe for individuals, communities, economies, and ecosystems around the world. While efforts to reduce emissions and adapt to climate impacts are the first line of defense, researchers are exploring other options to reduce warming. Solar geoengineering strategies are designed to cool Earth either by adding small reflective particles to the upper atmosphere, by increasing reflective cloud cover in the lower atmosphere, or by thinning high-altitude clouds that can absorb heat. While such strategies have the potential to reduce global temperatures, they could also introduce an array of unknown or negative consequences. This report concludes that a strategic investment in research is needed to enhance policymakers' understanding of climate response options. The United States should develop a transdisciplinary research program, in collaboration with other nations, to advance understanding of solar geoengineering's technical feasibility and effectiveness, possible impacts on society and the environment, and social dimensions such as public perceptions, political and economic dynamics, and ethical and equity considerations. The program should operate under robust research governance that includes such elements as a research code of conduct, a public registry for research, permitting systems for outdoor experiments, guidance on intellectual property, and inclusive public and stakeholder engagement processes.
Keywords: Earth Sciences; Environment and Environmental Studies; Engineering and Technology

Strategies for Developing, Implementing, and Sustaining Sexual Harassment Bystander Intervention Programs for Faculty, Staff, and Graduate Students - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
To address the persistent problem of sexual harassment within higher education, research suggests that environments need to convey that sexual harassment is not a norm and actively discourage it when it does occur. One approach that researchers have identified as helping to create such environments is bystander intervention programs, which prepare and equip individuals to interrupt and intervene when harassing behavior occurs. This paper explores bystander intervention training approaches that are designed for the complex work environments within higher education, and considers how to apply the principles of bystander intervention to the experiences and environments of faculty, staff, and graduate students., Institutions within the Action Collaborative were asked a standard set of questions to learn about their experiences with commitment and buy-in from leadership, details on how the trainings were developed and what audience it was targeted to, and how the training programs were evaluated. The paper summarizes responses from seven of these institutions and ends with a call for additional research and action. This individually-authored issue paper was created by members of the Prevention Working Group of the Action Collaborative on Preventing Sexual Harassment in Higher Education to understand how institutions are addressing the gap in bystander intervention training for faculty, staff, and graduate students. The Action Collaborative on Preventing Sexual Harassment in Higher Education of the National Academies of Sciences, Engineering, and Medicine brings together academic and research institutions and key stakeholders to work toward targeted, collective action on addressing and preventing sexual harassment across all disciplines and among all people in higher education. The Action Collaborative includes four working groups (Prevention, Response, Remediation, and Evaluation) that identify topics in need of research, gather information, and publish resources for the higher education community.
Keywords: Education

Incorporating Climate Change and Climate Policy into Macroeconomic Modeling: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Macroeconomic models, essential for decision making and federal budget planning, may not appropriately consider the wide breadth of climate-related impacts that potentially have large macroeconomic significance. Challenges integrating climate factors into macroeconomic analyses can stem from the complexity of macroeconomics, climate science, policy instruments, and their interactions. Although economists have made progress in developing tools to understand climate-related impacts on the macroeconomy, much of the climate and macroeconomic research has historically been conducted in disciplinary silos that can limit a holistic understanding of climate-related impacts on the macroeconomy. The National Academies of Sciences, Engineering, and Medicine, under the auspices of the Roundtable on Macroeconomics and Climate-Related Risks and Opportunities, convened a workshop on June 14-15, 2023, to consider current macroeconomic models and suggest opportunities that may improve the incorporation of climate-related factors into macroeconomic modeling. Through panels of invited speakers and an interactive breakout discussion, the workshop explored an array of macroeconomic models and potential pathways to integrate some of the physical and transition effects of climate change. This publication summarizes the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies; Industry and Labor

Climate-Resilient Supply Chains: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
As the COVID-19 pandemic has demonstrated, the global supply chain is vulnerable to major disruptions from unanticipated events, yet no threat to the functioning of essential supply chains looms larger than the growing number of extreme weather events resulting from climate change. Indeed, the characteristics of today's supply chains - their dependence on shipping and air transport, specialized inputs sourced from specific locations spread worldwide, and reduced inventories tied to just-in-time production - make them especially vulnerable to disruption from climate risks. With the goal of protecting global trade worth almost $20 trillion annually against such disruptions, supply chain executives and researchers who study global supply chains are now starting to focus on ways of increasing supply chain resilience in a world buffeted by climate change. To explore ongoing efforts to create climate-resilient supply chains, the Science and Technology for Sustainability program at the National Academies of Sciences, Engineering, and Medicine, held a two-day virtual workshop on September 27-28, 2021.
Keywords: Environment and Environmental Studies

Climate and Health Challenges Posed by Black Carbon: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In October 2012, the National Academies of Sciences, Engineering, and Medicine and the Russian Academy of Sciences held a workshop in Moscow, Russia, on the Challenges of Black Carbon (BC). The workshop was carried out pursuant to the long-standing bilateral NAS-RAS Agreement on Cooperation in the Fields of Science, Engineering, and Medicine and attracted considerable interest among scientists and policy experts. More than 50 Russian and American scientists and specialists participated. The participants addressed many areas of scientific interest regarding BC dispersal, particularly in the northern latitudes, and called for continued cooperation between the academies on BC-related issues. A second workshop was held in April 2016 and included 29 technical presentations from individuals at 11 Russian and 8 U.S. institutions. The primary goals of the workshop were to learn about current research on BC and to identify opportunities for scientific and technical collaboration among experts in the United States and Russia.
Keywords: Earth Sciences; Health and Medicine

Partnerships and Cross-Sector Collaboration Priorities to Support Climate Research and Policy: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
As global mean temperatures rise and extreme climate and weather events increase in frequency and intensity, the severity of the climate situation and its potential impacts on human well-being - particularly of the world's most vulnerable populations - is strikingly evident. Research and policy responses to address climate change are required to meet U.S. targets set for the coming decades, which include a reduction of 50 to 52 percent of greenhouse gas emissions by 2030 and net-zero emissions by 2050. In coordination with other activities on climate, energy, and environmental and human health across the National Academies of Sciences, Engineering, and Medicine, the Government-University-Industry Research Roundtable convened a series of five workshops in June and July of 2021 to discuss opportunities for enhancing U.S. scientific and technological approaches to climate research and policy through cross-sector collaboration and partnerships, and to examine the impacts of climate policy on economic development, inequality, and international competitiveness. This document summarizes the presentations and discussions at the five workshops.
Keywords: Policy for Science and Technology; Environment and Environmental Studies

Motivating Local Climate Adaptation and Strengthening Resilience: Making Local Data Trusted, Useful, and Used - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Local communities are already experiencing dire effects caused by climate change that are expected to increase in frequency, intensity, duration, and type. Public concern about climate-related challenges is increasing, available information and resources on climate risks are expanding, and cities across the country and the globe are developing approaches to and experience with measures for mitigating climate impacts. Building and sustaining local capacities for climate resilience requires both resilient physical and social infrastructure systems and inclusive, resilient communities. At the request of the Federal Emergency Management Agency, Motivating Local Climate Adaptation and Strengthening Resilience provides guidance for active and ongoing efforts to move science and data into action and to enable and empower applied research that will strengthen capacities for hazard mitigation and resilience in communities, across the nation, and around the world.
Keywords: Environment and Environmental Studies

Solar Geoengineering Research Governance: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Despite efforts to reduce greenhouse gas emissions, many countries’ efforts reduce emissions are falling short of targets needed to limit global warming and its associated negative impacts. While there is widespread agreement that continued efforts to reduce emissions and adapt to climate change are paramount, there is growing interest in “climate intervention” or “geoengineering” approaches, including those that reduce global warming by reflecting sunlight to cool Earth. In a workshop held in September 2019, the National Academies convened experts to inform a larger study on solar geoengineering. Workshop participants discussed the governance of research at international, national, and sub-national scales and explored research governance mechanisms that might be applied to climate intervention research. This publication summarizes the presentations and discussions for the workshop.
Keywords: Earth Sciences; Engineering and Technology

Developing a Research Agenda for Solar Geoengineering Strategies: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Despite efforts to reduce greenhouse gas emissions, many countries’ efforts reduce emissions are falling short of targets needed to limit global warming and its associated negative impacts. While there is widespread agreement that continued efforts to reduce emissions and adapt to climate change are paramount, there is growing interest in “climate intervention” or “geoengineering” approaches, including those that reduce global warming by reflecting sunlight to cool Earth. In a workshop held in August 2019, the National Academies convened experts to inform a larger study on solar geoengineering. Workshop participants discussed the current status of, and future directions for research on solar geoengineering strategies, including stratospheric aerosol injection, marine cloud brightening, and cirrus cloud thinning. This publication summarizes the presentations and discussions for the workshop.
Keywords: Earth Sciences; Engineering and Technology

Next Generation Earth Systems Science at the National Science Foundation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The National Science Foundation (NSF) has played a key role over the past several decades in advancing understanding of Earth's systems by funding research on atmospheric, ocean, hydrologic, geologic, polar, ecosystem, social, and engineering-related processes. Today, however, those systems are being driven like never before by human technologies and activities. Our understanding has struggled to keep pace with the rapidity and magnitude of human-driven changes, their impacts on human and ecosystem sustainability and resilience, and the effectiveness of different pathways to address those challenges. Given the urgency of understanding human-driven changes, NSF will need to sustain and expand its efforts to achieve greater impact. The time is ripe to create a next-generation Earth systems science initiative that emphasizes research on complex interconnections and feedbacks between natural and social processes. This will require NSF to place an increased emphasis on research inspired by real-world problems while maintaining their strong legacy of curiosity driven research across many disciplines – as well as enhance the participation of social, engineering, and data scientists, and strengthen efforts to include diverse perspectives in research.
Keywords: Earth Sciences

Attacks on Scientists and Health Professionals During the Pandemic: Proceedings of a Symposium—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Scientists and health professionals have long been targeted in connection with their professional work. Though this problem preceded the pandemic, it has emerged as a major concern, both in the United States and globally, as a result of COVID-19. Since the onset of the pandemic, scientists and health professionals have been subjected to threats and other attacks - online and offline - resulting from their efforts to combat the spread of COVID-19 with public health interventions and information. Reports of violence - carried out by numerous actors, including governments, groups, and individuals - are wide ranging and have come from all over the globe. In some cases, scientists, health professionals, and other groups have been targeted by multiple sources simultaneously, putting them at heightened risk of harm. Beginning September 1, 2022, the U.S. National Academies of Sciences, Engineering, and Medicine Committee on Human Rights hosted five webcasts examining the global problem of COVID-19-related attacks on researchers and health professionals, along with concerns regarding repression of information during the pandemic and implications for internationally protected rights. Topics included the targeting of scientists and public health professionals for providing evidence-based health information, global patterns of violence against health personnel, censorship and the right to information, science communication and human rights amid public health emergencies, and constructing a human rights framework for online health-related speech. This Proceedings of a Symposium-in Brief provides a high-level summary of the issues discussed during the series.
Keywords: Policy for Science and Technology

Assessment of the SBIR and STTR Programs at the National Institutes of Health - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The National Institutes of Health (NIH) asked the National Academies of Sciences, Engineering, and Medicine to conduct a quadrennial review of its Small Business Innovation Research (SBIR) and Small Business Technology Transfer (STTR) programs, in accordance with a legislative mandate. Using quantitative and qualitative analyses of data, this report reviews the operations and outcomes stemming from NIH's SBIR/STTR awards. Drawing on published research and conducting new analyses based on both publicly available data and applicant data provided by NIH, Assessment of the SBIR and STTR Programs at the National Institutes of Health analyzes (1) the effectiveness of NIH's processes and procedures for selecting SBIR and STTR awardees; (2) the effectiveness of NIH's outreach to increase SBIR and STTR applications from small businesses that are new to the programs, from underrepresented states, and from woman-owned and minority-owned businesses; (3) collaborations between small businesses and research institutions resulting from the programs; and (4) a range of direct economic and health care impacts attributable to the programs.
Keywords: Policy for Science and Technology

Sexual Harassment of Women: Climate, Culture, and Consequences in Academic Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Over the last few decades, research, activity, and funding has been devoted to improving the recruitment, retention, and advancement of women in the fields of science, engineering, and medicine. In recent years the diversity of those participating in these fields, particularly the participation of women, has improved and there are significantly more women entering careers and studying science, engineering, and medicine than ever before. However, as women increasingly enter these fields they face biases and barriers and it is not surprising that sexual harassment is one of these barriers. Over thirty years the incidence of sexual harassment in different industries has held steady, yet now more women are in the workforce and in academia, and in the fields of science, engineering, and medicine (as students and faculty) and so more women are experiencing sexual harassment as they work and learn. Over the last several years, revelations of the sexual harassment experienced by women in the workplace and in academic settings have raised urgent questions about the specific impact of this discriminatory behavior on women and the extent to which it is limiting their careers. Sexual Harassment of Women explores the influence of sexual harassment in academia on the career advancement of women in the scientific, technical, and medical workforce. This report reviews the research on the extent to which women in the fields of science, engineering, and medicine are victimized by sexual harassment and examines the existing information on the extent to which sexual harassment in academia negatively impacts the recruitment, retention, and advancement of women pursuing scientific, engineering, technical, and medical careers. It also identifies and analyzes the policies, strategies and practices that have been the most successful in preventing and addressing sexual harassment in these settings.
Keywords: Policy for Science and Technology; Behavioral and Social Sciences

China-U.S. Scientific Engagement: Key Issues and Possible Solutions for Sustainability and Planetary Health: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Scientists in China and in the United States have worked collaboratively, both formally and informally, for years to address their shared sustainability challenges. To further this engagement, the U.S. National Academies of Sciences, Engineering, and Medicine and the Chinese Academy of Sciences convened a workshop on June 20-21, 2023 focused on identifying priority areas for scientific collaboration to promote sustainability and planetary health in China and the United States. Participants gathered at the National Academies Beckman Center in Irvine, California, as well as virtually to discuss a subset of the field, including ecosystems and planetary health; air pollution and planetary health; urbanization and circular systems towards planetary health; planetary health, health emergencies, and climate change; and key priorities and international cooperation for planetary health. This publication summarizes the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies

Location Data in the Context of Public Health, Research, and Law Enforcement: An Exploration of Governance Frameworks: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On June 8-9, 2022, an ad hoc planning committee under the auspices of the National Academies of Sciences, Engineering, and Medicine's Committee on Science, Technology, and Law hosted a workshop, Location Data in the Context of Public Health, Research, and Law Enforcement: An Exploration of Governance Frameworks. The workshop examined the collection, interpretation, and use of location data by government, academia, and industry. This publication summarizes the presentations and discussion of the workshop.
Keywords: Computers and Information Technology

Mentoring of Black Graduate and Medical Students, Postdoctoral Scholars, and Early-Career Faculty in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On December 7 and 8, 2020, the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop that examined how to strengthen mentoring and advising of Black students and professionals in science, engineering, and medicine. Presenters included faculty deans, social scientists who are experts in organizational and professional development, and program implementers. Throughout the workshop, individual presenters highlighted evaluation criteria used by successful pipeline programs, including statistics on recruitment, retention, and advancement; career and leadership accomplishments; and awards and publications. This publication summarizes the presentations and discussions of the workshop.
Keywords: Education

Science, Technology, and Health Capabilities Within the Department of State and USAID at an Inflection Point: Proceedings of a Workshop-in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The need for U.S. foreign and development policy to be informed by science, technology, and health has perhaps never been more important. Amidst the COVID-19 pandemic, additional global challenges such as climate change, rapidly emerging technologies, and geopolitical competition underscore the importance of strong integration of science, technology, and health into diplomatic and development missions for American prosperity and security. In September 2020, the National Academies of Sciences, Engineering, and Medicine, held a workshop to identify approaches to strengthen science, technology, and health capabilities at the U.S. Department of State and the U.S. Agency for International Development over the next 5 to 10 years. The workshop featured brief presentations by leading American experts from government agencies, universities, research centers, non-governmental organizations, and the private sector, and several leaders from abroad who are actively integrating science and technology developments in the foreign policies of their countries. This publication is a summary of the presentations and the discussions during the workshop.
Keywords: Policy for Science and Technology

Knowledge-Action Systems for Seasonal to Interannual Climate Forecasting: Summary of a Workshop - National Research Council (The National Academies Press, 2005)
The National Academies' Roundtable on Science and Technology for Sustainability hosted a workshop "Knowledge-Action Systems for Seasonal to Interannual Climate Forecasting" in 2004 to discover and distill general lessons about the design of effective systems for linking knowledge with action from the last decade's experience with the production and application of seasonal to interannual climate forecasts. Workshop participants described lessons they had learned based on their experiences developing, applying, and using decision support systems in the United States, Columbia, Brazil, and Australia. Some of the key lessons discussed, as characterized by David Cash and James Buizer, were that effective knowledge-action systems: define and frame the problem to be addressed via collaboration between knowledge users and knowledge producers; tend to be end-to-end systems that link user needs to basic scientific findings and observations; are often anchored in "boundary organizations" that act as intermediaries between nodes in the system - most notably between scientists and decision makers; feature flexible processes and institutions to be responsive to what is learned; use funding strategies tailored to the dual public/private character of such systems; and require people who can work across disciplines, issue areas, and the knowledge–action interface.
Keywords: Earth Sciences

Psychological Factors That Contribute to the Dearth of Black Students in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Efforts over the last several decades to increase the participation and leadership of Black men and women in the scientific and medical workforce have had limited results. Despite many individual successes, the number of Black professionals in science, engineering, and medicine (SEM) fields has not reached a level that corresponds with African American representation in the country at large. Structural racism affects progress at all stages along the pathway - from young children through graduate and medical students through faculty and clinicians at all levels. Beyond entry into educational programs or recruitment into workplaces seeking to diversify, challenges persist to achieve equity and inclusion for Black males and females. Moreover, psychological barriers confound the engagement of Black men and women in SEM fields. To explore these issues and suggest solutions, the National Academies of Sciences, Engineering, and Medicine launched the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine. Over the past 2 years, the Roundtable has convened workshops on K-12 education, the impact of COVID-19, financial burdens to pursuing SEM careers, and other topics. Sessions during each of these workshops identified psychological factors related to those specific topics. To have a more targeted discussion, the Roundtable convened a virtual workshop on September 14-15, 2021. As summarized in this proceedings, panelists and participants identified policies and practices that perpetuate these factors and explored solutions toward achieving and maintaining wellness, especially among students and young professionals.
Keywords: Education; Health and Medicine

Mental Health, Substance Use, and Wellbeing in Higher Education: Supporting the Whole Student - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Student wellbeing is foundational to academic success. One recent survey of postsecondary educators found that nearly 80 percent believed emotional wellbeing is a "very" or "extremely" important factor in student success. Studies have found the dropout rates for students with a diagnosed mental health problem range from 43 percent to as high as 86 percent. While dealing with stress is a normal part of life, for some students, stress can adversely affect their physical, emotional, and psychological health, particularly given that adolescence and early adulthood are when most mental illnesses are first manifested. In addition to students who may develop mental health challenges during their time in postsecondary education, many students arrive on campus with a mental health problem or having experienced significant trauma in their lives, which can also negatively affect physical, emotional, and psychological wellbeing. The nation's institutions of higher education are seeing increasing levels of mental illness, substance use and other forms of emotional distress among their students. Some of the problematic trends have been ongoing for decades. Some have been exacerbated by the COVID-19 pandemic and resulting economic consequences. Some are the result of long-festering systemic racism in almost every sphere of American life that are becoming more widely acknowledged throughout society and must, at last, be addressed. Mental Health, Substance Use, and Wellbeing in Higher Education lays out a variety of possible strategies and approaches to meet increasing demand for mental health and substance use services, based on the available evidence on the nature of the issues and what works in various situations. The recommendations of this report will support the delivery of mental health and wellness services by the nation's institutions of higher education.
Keywords: Health and Medicine; Education